Ar-Ar age constraints on the timing of Havre Trough opening and magmatism. Issue 3 (3rd July 2019) - Wysoczanski, Richard; Leonard, Graham; Gill, James; Wright, Ian; Calvert, Andrew; McIntosh, William; Jicha, Brian; Gamble, John; Timm, Christian; Handler, Monica; Drewes-Todd, Elizabeth; Zohrab, Alex
ABSTRACT: The age and style of opening of the Havre Trough back-arc system is uncertain due to a lack of geochronologic constraints for the region. 40 Ar/ 39 Ar dating of 19 volcanic rocks from across the southern Havre Trough and Kermadec Arc was conducted in three laboratories to provide age constraints on the system. The results are integrated and interpreted as suggesting that this subduction system is young (<2 Ma) and coeval with opening of the continental Taupo Volcanic Zone of New Zealand. Arc magmatism was broadly concurrent across the breadth of the Havre Trough.